Current practices for viability testing of cryopreserved cord blood products: an international survey by the cellular therapy team of the Biomedical Excellence for Safer Transfusion (BEST) Collaborative. Issue 9 (11th September 2018) - Takanashi, Minoko; Selogie, Eileen; Reems, Jo‐Anna; Stroncek, David; Fontaine, Magali J.; Girdlestone, John; Garritsen, Henk S. P.; Young, Pampee; McKenna, David H.; Szczepiorkowski, Zbigniew M.; ,
Abstract : BACKGROUND: Viability testing is a common practice in laboratories. The goal of this study was to ascertain current laboratory practices internationally for performing viability testing for cryopreserved cord blood (CB) products and glean information about how to standardize the method to improve interlaboratory reproducibility. STUDY DESIGN AND METHODS: A survey to evaluate current laboratory practices for viability testing was designed and distributed internationally. The question topics included sampling and testing methods, responses to unexpected results, and the rating of the reliability of the CB quality tests, together with expectations for standardization. RESULTS: There were 32 respondents to the survey, of whom 28 responded to the more detailed questionnaire about viability methods. Overall, responses indicated that various stains were used among the laboratories, and when multiple sites used the same viability stain the methods differed. The majority of the respondents were in favor of standardizing the viability testing methods. A wide variety of preferences were communicated about how to standardize the method, but a majority did advocate the use of 7‐aminoactinomycin D (7‐AAD) with flow cytometry. CONCLUSIONS: The survey results revealed a variety of tests and inconsistent interlaboratory practices for performing the viability assay. Flow cytometry with a 7‐AAD dye was suggested as a first step toward standardization.